2019
DOI: 10.1016/j.seizure.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Scalp EEG high frequency oscillations as a biomarker of treatment response in epileptic encephalopathy with continuous spike-and-wave during sleep (CSWS)

Abstract: We investigated whether the presence of interictal scalp EEG high frequency oscillations (HFOs) in children with epileptic encephalopathy with continuous spike-and-wave during sleep (CSWS) can predict seizure and cognitive outcome after steroid therapy. Methods: Twenty-two children with CSWS were prospectively enrolled and received methylprednisolone therapy. Interictal scalp HFOs, spike wave index (SWI) and intelligence quotient (IQ) were assessed before and after the treatment. The children were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…After the successful treatments (medications or surgery), the HFO-related values decreased. Such findings were consistent with the prior studies showing active epilepsy correlated with the presence of scalp EEG HFOs in infantile spasms (Kobayashi et al, 2015), benign Rolandic epilepsy (Kobayashi et al, 2011;van Klink et al, 2016), and epilepsy with continuous spikes and waves during slow-wave sleep (CSWS) (Cao et al, 2019;Kobayashi et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After the successful treatments (medications or surgery), the HFO-related values decreased. Such findings were consistent with the prior studies showing active epilepsy correlated with the presence of scalp EEG HFOs in infantile spasms (Kobayashi et al, 2015), benign Rolandic epilepsy (Kobayashi et al, 2011;van Klink et al, 2016), and epilepsy with continuous spikes and waves during slow-wave sleep (CSWS) (Cao et al, 2019;Kobayashi et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have shown EEG fast activities can be recorded non-invasively from the scalp recordings (Andrade-Valenca et al, 2011;Bernardo et al, 2018;Kobayashi et al, 2004;Kobayashi et al, 2015;Kramer et al, 2019;Nariai et al, 2017;Nariai et al, 2018;Pizzo et al, 2016;Wu et al, 2008). Scalp EEG HFOs have the potential to localize seizure onset zones (Andrade-Valenca et al, 2011;Bernardo et al, 2018;Nariai et al, 2017;Tamilia et al, 2020), and to monitor disease activity in epileptic spasms (Kobayashi et al, 2015), Rolandic epilepsy (Kobayashi et al, 2011;van Klink et al, 2016), and epileptic encephalopathy with continuous spike-and-wave during sleep (CSWS) (Cao et al, 2019;Kobayashi et al, 2010). Additionally, HFOs coupled with slow-wave activity strongly localize to epileptic brain regions in children with infantile spasms and other types of focal epilepsy in invasive monitoring (Iimura et al, 2018;Motoi et al, 2018;Nonoda et al, 2016;Song et al, 2017;Weiss et al, 2016) and may reflect disease activity in scalp EEG in epileptic spasms (Bernardo et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Dezhi et al studied HFOs in 22 children with persistent spike-wave encephalopathy during sleep who received methylprednisolone treatment. HFOs disappeared from scalp EEG in children treated with hormones, but children with no response or recurrence after hormone therapy showed persistent HFOs ( Cao et al, 2019 ). In the study, the interaction of curative efficacy × frequency and the interaction of curative efficacy × state are statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] At present, most research on scalp HFOs has only analyzed ripple band. Recently, some studies have applied scalp HFOs to locate epilepsy generators [24][25][26][27] and to mirror disease activity and treatment response, 23,28 as well as to differentiate distinct disease entities. 29 Nariai et al investigated the diagnostic utility of scalp HFO in IS, 30 and found that increased rate of HFOs and coupling between HFOs and slow-wave activity (SWA) are associated with active epileptic spasms.…”
Section: Introductionmentioning
confidence: 99%